1984
DOI: 10.1111/j.1399-3011.1984.tb02739.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide models for β‐turns.

Abstract: The circular dichroism spectra of four β‐turn model peptides, Z‐Aib‐Pro‐Aib‐Pro‐OMe (1), Piv‐Pro‐Aib‐NHMe (2), Piv‐Pro‐D‐Ala‐NHMe (3) and Piv‐Pro‐Val‐NHMe (4) have been examined under a wide range of solvent conditions, using methanol, hexafluoroisopropanol and cyclohexane. Type I and Type II β‐turns have been observed for peptides 1 and 2 respectively, in the solid state, while the Pro‐D‐Ala sequence adopts a Type II β‐turn in a related peptide crystal structure. A class C spectrum is observed for 1 in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 31 publications
(2 reference statements)
1
17
0
Order By: Relevance
“…These observations confirm that the signals at ∼ 198 and 230 nm are independent. It is also suggested that the band at 230 nm could correspond to a β‐turn conformation of the VPGF segment, as the presence of a PG dipeptide motif is commonly responsible for the formation of a turn and that a weak negative band between 220 and 230 nm is characteristic of a n → π* electronic transition for a β‐turn …”
Section: Resultsmentioning
confidence: 99%
“…These observations confirm that the signals at ∼ 198 and 230 nm are independent. It is also suggested that the band at 230 nm could correspond to a β‐turn conformation of the VPGF segment, as the presence of a PG dipeptide motif is commonly responsible for the formation of a turn and that a weak negative band between 220 and 230 nm is characteristic of a n → π* electronic transition for a β‐turn …”
Section: Resultsmentioning
confidence: 99%
“…The spectrum in TFE (solid line in panel A) shows a single minimum at ∼ 225 nm. The MeOH spectrum (solid line in panel B) shows a minimum ∼210 nm, a shoulder at 225 nm, a cross over at 205 nm and a positive band at 197 nm suggests that the peptide folds into β‐turn conformation . The spectrum in HFIP (solid line in panel C) shows a broad minimum at ∼ 225 nm and a sharper negative band at 197 nm.…”
Section: Resultsmentioning
confidence: 97%
“…Further information on the change of supramolecular arrangements of IQSPHFF was obtained from the FTIR studies. The literature reports that the most informative frequency ranges are as follows (i) 3200–3400 cm −1 , corresponding to the N—H stretching vibrations of the peptide and N‐protecting urethane groups, and (ii) 1800–1600 cm −1 , corresponding to the CO stretching vibrations of the peptide . Peaks at around 1685 cm −1 can be assigned to the amide I band, and those peak at about 1454 cm −1 are associated with the amide II band .…”
Section: Resultsmentioning
confidence: 99%